Treating Every Needle in the Haystack: Hyperammonemic Encephalopathy and Severe Malnutrition After Bariatric Surgery—A Case Report and Review of the Literature. (2nd September 2014) - Singh, Sanjeev; Suresh, Swetha; McClave, Stephen A.; Cave, Matt
Abstract : Neurologic complications are not uncommon following bariatric surgery. Hyperammonemic encephalopathy (HAE) due to an acquired or unmasked urea cycle deficit is among the rarest of these. Pediatric nutrition support specialists are familiar with recognizing urea cycle deficits, but adult specialists may not be. Here we present a case of a patient initially misdiagnosed with cirrhosis who presented with recurrent HAE 4 years after Roux‐en‐Y gastric bypass. She was diagnosed with a proximal urea cycle deficit and severe protein calorie malnutrition. The patient recovered with specialized nutrition and medical support targeting this condition. A literature review indicates multiple fatalities from this condition, indicating the importance of early diagnosis and appropriate nutrition support.